Effects of row spacing and lineal sowing density of kenaf (Hibiscus cannabinus L.) yield components in the north-west of Argentina - Acreche, M.M.=700 1 Gray, L.N.; Collavino, N.G.; Mariotti, J.A.
(Es, En)
ilus., 19 ref.
Keywords: HIBISCUS CANNABINUS; COMPETENCIA BIOLOGICA; ESPACIAMIENTO; ARGENTINA; ARGENTINA; KENAF